2012
DOI: 10.1111/j.1538-7836.2011.04608.x
|View full text |Cite
|
Sign up to set email alerts
|

Is atrial fibrillation associated with pulmonary embolism?

Abstract: Summary. Background: A pulmonary embolism (PE) is thought to be associated with atrial fibrillation (AF). Nevertheless, this association is based on weak data. Objectives: To assess whether the presence of AF influences the clinical probability of PE in a cohort of patients with suspected PE and to confirm the association between PE and AF. Patients/ methods: We retrospectively analyzed the data from two trials that included 2449 consecutive patients admitted for a clinically suspected PE. An electrocardiograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 24 publications
3
20
0
1
Order By: Relevance
“…Gex et al reported that overall 30-day mortality rate was 4.3% between 2004 and 2009, compared with 7.6% in 2002 and 2003, and 11.7% in 1997 and 1999 [100]. Our study found the overall 30-day mortality rate of 5.8% and the pooled OR of 0.668, showing that MIO to be advantageous than OE in reducing mortality.…”
Section: Discussionsupporting
confidence: 44%
“…Gex et al reported that overall 30-day mortality rate was 4.3% between 2004 and 2009, compared with 7.6% in 2002 and 2003, and 11.7% in 1997 and 1999 [100]. Our study found the overall 30-day mortality rate of 5.8% and the pooled OR of 0.668, showing that MIO to be advantageous than OE in reducing mortality.…”
Section: Discussionsupporting
confidence: 44%
“…AF has also been linked to prior VTE via several other lines of evidence [4], including a longitudinal analysis of the Longitudinal Health Insurance Database 2000 [24], two case-control studies [25, 26], registry studies of PE patients [4], small clinical studies [10, 11], and autopsy studies [27]. In the present paper we conducted analyses by VTE classification (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The reported prevalence of atrial fibrillation in acute pulmonary embolism (PE) varies widely, and most studies are focused on diagnostic purposes . Moreover, as the temporal sequence of events has not been determined in these studies, the question of cause and effect remains unanswered.…”
Section: Introductionmentioning
confidence: 99%